Trabalho doméstico não-remunerado: rupturas, continuidades e adaptações do trabalho doméstico e de cuidados - Oliveira, Heloisa Helena de Sousa Franco (2021)
In this thesis, we present an analysis of the configurations of housework and care work, seeking to answer the question: how do women operationalize housework and care work in their daily lives? The concepts of the sexual division of labor, productive and reproductive work and housework and care work are the theoretical basis that support this study. Thus, we investigated, from the experience of 5 women, in the city of João Pessoa, the social relations that are established from this issue, with the main goal of understanding how some women operationalize housework and care work, whom they appeal or activate. Therefore, we analyze how the daily dynamics related to reproductive work are constituted, verifying how these women perceive the housework and care work that touch their lives and if there are alienation processes along this path. For this purpose, in addition to bibliographic review and data collection, specific techniques to qualitative research, such as direct observation, life stories and application of semi-structured interviews, in field work with women of different profiles, from the city of João Pessoa (PB). The results reveal the permanence of housework and care work still as a task, mostly, of women; small changes in family arrangements for the performance of this work, due to variables such as: marital status, income and generation; the recognition of the importance of this work by women, the discomfort of women with its social devaluation and the burden that falls on their lives; of all the chores included in the scope of housework and care work, those concerning childrearing are the ones that demand the most time from women. We found that, in this process, women developed, from their experiences, a complex network of reproductive work, in order to resolve the dilemma of the lack of responsibility of men and the State regarding to the sharing of housework and care work, creating what we call reproductive chains of work.